2009
DOI: 10.1007/s10681-009-9889-4
|View full text |Cite
|
Sign up to set email alerts
|

Somaclonal variation in sugarcane through tissue culture and evaluation for quantitative and quality traits

Abstract: Eight genotypes of Saccharum officinarum were crossed with Saccharum spontaneum and 14 genotypes of S. officinarum were crossed with Erianthus arundinaceus. A total of 39 hybrids were evolved. These 39 hybrids were raised in the field and used as donor clones for in vitro culture studies. Plantlets were regenerated from 1-month-old callus. The grown up plants were transplanted to well prepared field, to study the variations generated for the biometric as well as for biochemical characters. There were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
0
10
0
3
Order By: Relevance
“…Many authors have concluded that in vitro culture can be applied as a complementary system to conventional breeding to improve its efficiency, create variants and increase variations within sub-clonal populations (Doule et al, 2008;Rajeswari et al, 2009). These somaclonal Krishnamurthi and Tlaskal (1974) and Heinz et al 1977) Mosaic virus (SCMV) Nickell and Heinz (1973), Oropeza et al (1975); Oropeza and de Garcia (1975) Red rot (Colletotrichum falcatum) Heinz (1973), Larkin and Scowcroft (1983) Krishnamurthi and Tlaskal (1974) Insect pest resistance Stalk borer (Diatraea saccharalis) White and Irvine (1987) Abiotic stress Salt tolerance Saif-Ur-Rasheed et al (2001), Patade et al (2005) and Gandonou et al (2006) Yield/growth components Improved erect nature of stalks, stalk diameter, length, colour and density, leaf colour, foliar characters, auricle length, bud groove, bud shape and size, flowering, cane yield, tillering, high silicate deposits on leaf surface and differences in growth habits, higher Brix and sucrose content Heinz and Mee (1969), Khan et al (2002), Abo-Elwafa (2004), Doule et al (2008) and Rajeswari et al (2009) variations can be exploited by researchers in Kenya for rapid sugarcane improvement programs.…”
Section: Somaclonal Variation For Sugarcane Improvementmentioning
confidence: 99%
“…Many authors have concluded that in vitro culture can be applied as a complementary system to conventional breeding to improve its efficiency, create variants and increase variations within sub-clonal populations (Doule et al, 2008;Rajeswari et al, 2009). These somaclonal Krishnamurthi and Tlaskal (1974) and Heinz et al 1977) Mosaic virus (SCMV) Nickell and Heinz (1973), Oropeza et al (1975); Oropeza and de Garcia (1975) Red rot (Colletotrichum falcatum) Heinz (1973), Larkin and Scowcroft (1983) Krishnamurthi and Tlaskal (1974) Insect pest resistance Stalk borer (Diatraea saccharalis) White and Irvine (1987) Abiotic stress Salt tolerance Saif-Ur-Rasheed et al (2001), Patade et al (2005) and Gandonou et al (2006) Yield/growth components Improved erect nature of stalks, stalk diameter, length, colour and density, leaf colour, foliar characters, auricle length, bud groove, bud shape and size, flowering, cane yield, tillering, high silicate deposits on leaf surface and differences in growth habits, higher Brix and sucrose content Heinz and Mee (1969), Khan et al (2002), Abo-Elwafa (2004), Doule et al (2008) and Rajeswari et al (2009) variations can be exploited by researchers in Kenya for rapid sugarcane improvement programs.…”
Section: Somaclonal Variation For Sugarcane Improvementmentioning
confidence: 99%
“…The variability generated in-vitro in together with chemical mutagenesis can aid in varietal improvement program since the resulting variants are reported to yield superior as well as are resistant to various diseases, insect-pests and abiotic stresses (Rajeswari et al, 2009;Mallikarjun et al, 2008;Bidabadi et al, 2011). In-vitro induced variability is reported to be enhanced during callus culture as it leads to the greater departure from the organized growth (Karp, 1995;Jain, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As plantas jovens são fontes de tecido e seu uso, na cultura de tecido permite melhor preservação da variabilidade genética e possibilita preservar mais a integridade do genoma da planta (RAJESWARI et al, 2009;TAWAR et al, 2008). A regeneração de plantas de cana-de-açúcar a partir de explantes na presença de diferentes concentrações de reguladores de crescimento torna a utilização da folha jovem um material viável para germinação de uma planta inteira, devido à uniformidade e à menor taxa de variação somaclonal.…”
Section: Cultura De Tecidos E Regeneração De Plantas Transgênicas a Punclassified
“…A falta desta estabilidade é um dos principais obstáculos na micropropagação e os fatores como genótipo e a fonte dos explantes e o método de propagação vegetativa podem ocasionar a ocorrência de variação somaclonal nas plantas regeneradas. (STEINMACHER, 2007;RAJESWARI, 2009). Após 3 dias os discos foram transferidos para os seus respectivos meios de regeneração de plantas suplementados com geneticina (30 mg/L) para a seleção dos transformantes.…”
Section: Cultura De Tecidos E Regeneração De Plantas Transgênicas a Punclassified
See 1 more Smart Citation